In search of a better understanding of social presence: an investigation into how researchers define social presence. Issue 2 (4th May 2017) - Lowenthal, Patrick R.; Snelson, Chareen
Abstract: Research on social presence and online learning continues to grow. But to date, researchers continue to define and conceptualize social presence very differently. For instance, at a basic level, some conceptualize social presence as one of three presences within a Community of Inquiry, while others do not. Given this problem, we analyzed how researchers in highly cited social presence research defined social presence in an effort to better understand how they are defining social presence and how this might be changing over time. In this article, we report the results of our inquiry and conclude with implications for future research and practice.